Notification of crop varieties and registration of germplasm : Maize hybrid PMH 5 - Grewal, Maninder Singh (The Indian Journal of Genetics and Plant Breeding, 2016)
PMH 5 is a short duration single cross maize hybrid developed from a cross between two inbred parents LM 16 ( ) × LM 18 ( ) by the Punjab Agricultural University, Ludhiana, Punjab. It has been identified in 2010 and released in 2011 for cultivation in kharif season at national level in Zone V (Rajasthan, Madhya Pradesh, Gujarat and Chhattisgarh) by Central SubCommittee on Crop Standards. Notification and Release of Varieties for Agricultural Crops vide Notification No. S.O.632 (E), Sr. No. 18, The Gazette of India dated March 25, 2011. The female line, LM 16 [JS4-30-S8× (Tarun×MakkiSafed1yellow)-63-1g’-5F-#]- 12-S 8-## is second cycle line which has been developed from two inbred lines of the semi exotic pool through pedigree method. The male line LM18 is also second cycle line developed from local population (Kaloyey Local-S 8-#) of the semi exotic pool through pedigree method.